Association of Interleukin-28b- Rs8099917 with Response to Treatment with Interferon Α-2b & Ribavirin in C. Hepatitis C pts - Rahman Shah, Saifullah Khan Khalil, Umar Aleem, Falak Naz, Naimat Ullah, Najeeb Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the association of interleukin-28b- RS8099917 with response to treatment with interferon α-2b & ribavirin in chronic hepatitis C patients Methods: A case control study has been designed. Those who respond to standard therapy were classified as responders while those who didn’t respond to standard regimen were referred as non-responders. A total of 219 (95 males, 124 females) patients were recruited. All the demographics and biochemical data were recorded that includes age, ALT and viral load. The data were analyzed using SPSS version 16. Results: The data reveals that polymorphism of IL28B- RS8099917 does not affect the treatment outcome (p-value=0.65, OR=1.52). Similarly, both responders and non-responder groups were not consistent with HWE with p-value 0.9 and 0.23 respectively. Conclusion: polymorphism of IL28B- RS8099917 does not affect the treatment outcome Large multicenter studies must be conducted with large sample size to further validate our findings.